SOME PECULIARITIES OF MICROHARDNESS AND MICROFRAGILITY OF BORIDE LAYERS - V. F. Protasevich; V. V. Melnichenko (Литьë и металлургия, 2005)
Microhardness and microfragility of boride layers, received as a result of thermodiffusion strengthening, are studied and connection between microhardness, microfragility and degree of load at testings is established in this article.